(untitled) (Castilla. Estudios de Literatura, 2022)
This study focuses on Campo cerrado (1939), the first novel in el Laberinto mágico, the series by Max Aub centred on the Spanish Civil War and the 1934 Spanish Revolution, with the objective of analysing the artistic procedures from which the author performs a historic representation and elaborates a discourse which carries his political position in an exercise of commitment and social memory. Within the solid framework of the context, which traverses the Aubian literary creation and that cannot dodge Aub’s biography marked by displacements and based on the numerous studies devoted to his work, I look at the reconstruction and the polyphonic transmission of the narrated reality through instances and elements both derived from the extraliterary reality and formed within the text. Thus, I study the functions of fictionality, polyphony, hybridism and structure, as well as the use of rhetorical figures in the novel.